Virtual patient activity patterns for clinical learning. (3rd June 2015) - Ellaway, Rachel; Topps, David; Lee, Sonya; Armson, Heather
Summary Background Virtual patients are software tools that present learners with patient case situations and tasks. Some virtual patients take the learner through a guided case scenario, whereas others require learners to make diagnostic and therapeutic decisions. Much attention has been paid to the design of virtual patients and their use as standalone activities, but rather less attention has been paid to their use in broader educational activities. This article describes a series of activity patterns that make use of virtual patients. Context The article describes five patterns of clinical teaching activities that make use of virtual patients: independent study activities; collaborative group activities; blended activities; bridging activities; and reference activities. These patterns were developed inductively from the authors' teaching practices over a number of years. These are not the only activity patterns and designs that can make use of virtual patients but they are ones that have been found to be particularly useful over time and in many different contexts. Innovation Although the design of educational artifacts such as virtual patients is important, clinical teachers also need to consider the ways in which they are used. Different kinds of activity can employ different kinds of virtual patients of varying levels of complexity. An activity focus can allow clinical teachers to make more effective and broader use of virtual patients. Implications Virtual patients can be used for more than independent study. Clinical teachers are encouraged to explore the multitude of uses that virtual patients can be put to, and the ways in which activities can be constructed around them. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Different kinds of activity can employ different kinds of virtual patients, of varying levels of complexity </boxed-text>